Laboratory cyclic shear test to investigate the cyclic response of biopolymer-treated sand - Kim, Mintae; Park, Dong Yeup; Cho, Gye Chun; Han, Jin Tae; Chang, Ilhan (Smart Geotechnics for Smart Societies, 2023)
The effect of biopolymer-based soil treatment (BPST) on the liquefaction resistance of loose sand was investigated in this study. Cyclic simple shear (CSS) apparatus was used to assess the cyclic responses of untreated (natural) and gel-type biopolymer-treated sand specimens. Laboratory test results show that BPST is effective on improving both cyclic shear stress ratio (CSR) and cyclic shear resistance ratio (CRR) where BPST could be considered as a new ground improvement method for seismic mitigation and anti-liquefaction purposes.